UK Government funds better healthcare security. Issue 9 (September 2020) - Unknown
Abstract : Smaller organisations in the UK's healthcare sector are getting help from the Government to improve their security. A fund has been established by the Department for Digital, Culture, Media & Sport (DCMS) to help primary care providers (other than GPs) gain accreditation under the Cyber Essentials certification scheme.